The Prevalence and Characteristics of Exocrine Pancreatic Insufficiency in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis. (19th July 2022) - Zhang, Jun; Hou, Jiaying; Liu, Dechen; Lv, Yingqi; Zhang, Chi; Su, Xianghui; Li, Ling
Abstract : Background . Exocrine pancreatic insufficiency (EPI) is common in patients with type 2 diabetes. However, the prevalence of EPI varies significantly in different studies. Untreated EPI in these patients can adversely affect their nutrition and metabolism. The aim of this study is to estimate the pooled prevalence of EPI in patients with type 2 diabetes and to explore the potential risk factors. Methods . A systematic search was performed in PubMed, Web of Science, and Embase, which included studies meeting inclusion criteria from 1960 to 1 April 2022. Relevant articles were searched using the combination of Medical Subject Heading (MeSH) terms of "Type 2 diabetes" and "pancreatic exocrine insufficiency." The Stata 16.0 software was used for data analyses. The random-effects model was used to estimate the pooled prevalence rates and 95% CI using "metaprop program." Results . The pooled prevalence of EPI was 22% (95% CI: 15%–31%) in patients with type 2 diabetes and 8% (95% CI: 4%–14%) of them developed severe pancreatic insufficiency. In the subgroup analyses, the prevalence of EPI in type 2 diabetes was correlated with geographic location. The prevalence in Asian countries (35%, 95% CI: 22%–49%) is higher than in Europe (18%, 95% CI: 10%–29%) and Australia (9%, 95% CI: 4%–16%). Furthermore, patients with higher insulin requirements, who are more likely to be insulin-deficient, have a higher prevalence of EPI. The pooled prevalence was 27% (95% CI: 17%–37%) in type 2 diabetes with higher insulin requirement (1 group) and 15% (95% CI: 1%–40%) in patients with lower insulin requirement (2 group). In addition, the morbidity of severe EPI in the higher insulin requirement group (12%, 95% CI: 7%–19%) was sextuple as much as the lower insulin requirement group (2%, 95% CI: 0%–13%). EPI was more common in subjects younger than 60 compared with elderlies (25% vs. 19%). Conclusion . The prevalence of EPI in type 2 diabetes may be overestimated. Furthermore, the higher prevalence may be closely related to β -cell function. Endocrine disease therapy would potentially represent a novel therapeutic approach for patients with type 2 diabetes and EPI.